Customer Satisfaction towards TVS Bharath Motors in Aundipatti - Chitra, S.; Maheswari, J. (International Research Journal of Management, IT & Social Sciences, 2018)
This research analyses the satisfaction of the customer towards two-wheelers. The study was restricted only to Aundipatti talk. India is one of the largest manufacturers and producers of two-wheelers in the world. The brands such as Star city, Apache, Scooty pep plus, TVS-XL, TVS Jive, TVS Victor, are the popular brands in the Two wheeler. In this backdrop, the study has been undertaken customers satisfaction towards TVS Bharath motors in Aundipatty.